Formulation and Evaluation of Hair Tonic Gel Preparations Resistance Water Fraction N-Hexan Fruit Curm (Phoenix Dactylifera L.) - P, Chandra; J, Reveny; M, Nainggolan (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to formulate and evaluate of hair tonicgel preparations resistance water fraction n-hexan fruit curm (Phoenix dactylifera L.)Method: Dates are macerated with 80% ethanol, the extract is concentrated with a rotary evaporator dried with a freeze dryer, the extract is then fractionated with n-hexane. The concentrations used in the preparation of waterproof Hair tonic gel are 5, 7.5, 10 and 12.5% ​​fraction of n-hexane then compared to Hair Tonic from the market. Evaluation of gel preparations includes checking homogeneity, pH, viscosity, irritation, and stability. The animals used are male white rats.Results: The evaluation results of the waterproof gel evaluation on the fraction of n-hexane meet the SNI requirements. Hair tonic waterproof gel preparations yellow to dark brown, homogeneous for 12 weeks of storage at room temperature. The pH and viscosity are stable during 12 weeks of storage and do not irritate the skin. The best hair tonic waterproof hair growth gel growth activity at a concentration of 10%, n-hexane fraction (1.41 ± 0.07).Conclusion: The preparation of waterproof hair tonic gel n-hexane fraction (Phoenix dactylifera L.) has hair growth activity.